2015
DOI: 10.14202/vetworld.2015.723-726
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal helminths in Banaraja fowls reared in semi-intensive system of management in Mayurbhanj district of Odisha

Abstract: Aim:Studies on the prevalence of gastrointestinal helminths infection in Banaraja fowls of three blocks (Chandua, Shamakhunta and Bangriposi) of Mayurbhanj district in Odisha with respect to semi-intensive system of rearing.Materials and Methods:A total of 160 Banaraja birds (30 males and 130 females) belonging to two age groups (below 1 month age and above 1 month) were examined for the presence of different species of gastrointestinal helminth infection over a period of 1-year. The method of investigation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
2
5
2
Order By: Relevance
“…Females were more susceptible to endoparasites than males with a statistical significance. The results are contrary with other researchers where no statistical difference was reported [34,36,31] in backyard poultry. This could be due to the voracious feeding habits of female birds especially during egg production, then that of males which are largely selective in nature [34,36,31].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Females were more susceptible to endoparasites than males with a statistical significance. The results are contrary with other researchers where no statistical difference was reported [34,36,31] in backyard poultry. This could be due to the voracious feeding habits of female birds especially during egg production, then that of males which are largely selective in nature [34,36,31].…”
Section: Discussioncontrasting
confidence: 99%
“…The results are contrary with other researchers where no statistical difference was reported [34,36,31] in backyard poultry. This could be due to the voracious feeding habits of female birds especially during egg production, then that of males which are largely selective in nature [34,36,31]. Contrary Radfar et al [37]; Dar et al [33]; Momin et al [32] and Sheikh et al [38] reported more prevalence of parasitic infections in males than female birds.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…05). A similar finding was reported by earlier studies [3] , [31] , [32] . This could be attributed to the fact that both male and female birds in the environment were allowed to scavange freely for their daily needs of feed and water to supplement their dietary requirements.…”
Section: Discussionsupporting
confidence: 93%
“…These pathogens result in severe economic losses due to high morbidity, mortality and decreases production [2,3]. Tetrameres species, a proventricular parasite infects poultry by ingesting the intermediate hosts like amphipods or terrestrial insect or isopod containing third stage larva but, not seems to be highly specific in use of intermediate host, female worms are deep red in colour, and found embedded in the gastric mucosa/ glands and male worms are found free in lumen and usual nematode shape and occasionally reported [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%